2023
DOI: 10.3389/fimmu.2023.1274937
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab combined with anlotinib improves therapeutic efficacy in pulmonary sarcomatoid carcinoma with TMB-H and PD-L1 expression: a case report and literature review

Shugui Wu,
Shanlian Wu,
Xiaohong Liao
et al.

Abstract: BackgroundPulmonary sarcomatoid carcinoma (PSC) is a unique subtype of non-small cell lung cancer (NSCLC) with a high degree of malignancy and poor therapeutic effects. With the widespread use of immune checkpoint inhibitors (ICIs) in recent years, few studies have reported that immunotherapy is effective against PSC. As a multi-target anti-vascular targeting agent, anlotinib showed a better anti-tumor effect in various cancer species. The paper reported the therapeutic and side effects of pembrolizumab combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Doomblides, C et al showed a report on LSC that patients with high TMB had a median OS of 18 months, while the low TMB population had only 1.84 months (49). Other case reports of sarcomatoid carcinoma have also shown a longer survival time with a higher TMB (32,43,37,38).The median value of TMB in patients with sarcomatoid carcinoma of the head and neck was 4.34 (0.71-14.71) muts/Mb, and TMB was significantly higher in patients with advanced stages compared to those with early stages (20). However, the relationship between TMB and immunotherapy in patients with sarcomatoid carcinoma of the head and neck has not been confirmed.…”
Section: Discussionmentioning
confidence: 98%
“…Doomblides, C et al showed a report on LSC that patients with high TMB had a median OS of 18 months, while the low TMB population had only 1.84 months (49). Other case reports of sarcomatoid carcinoma have also shown a longer survival time with a higher TMB (32,43,37,38).The median value of TMB in patients with sarcomatoid carcinoma of the head and neck was 4.34 (0.71-14.71) muts/Mb, and TMB was significantly higher in patients with advanced stages compared to those with early stages (20). However, the relationship between TMB and immunotherapy in patients with sarcomatoid carcinoma of the head and neck has not been confirmed.…”
Section: Discussionmentioning
confidence: 98%
“…This case supports that timely surgery might lead to a good prognosis in PSC. Although there was not much evidence, the patient was given targeted therapy according to the gene result ( 14 , 16 , 26 ). Over-expression of PD-L1 is observed in more than half of pulmonary sarcomas, and the PD-1 inhibitor is gradually becoming a promising new method for the treatment of PSC patients ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although there was not much evidence, the patient was given targeted therapy according to the gene result ( 14 , 16 , 26 ). Over-expression of PD-L1 is observed in more than half of pulmonary sarcomas, and the PD-1 inhibitor is gradually becoming a promising new method for the treatment of PSC patients ( 26 , 27 ). A multidisciplinary comprehensive approach, integrating clinical staging, pathology, genetic testing, and other disciplines, may help in selecting more appropriate and precise treatments, and might be an important direction for improving patient prognosis ( 26 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…A chemoresistant patient achieved CR over 20 months after treatment with tislelizumab plus anlotinib ( 109 ). Similarly, good efficacy was observed in cases treated with anlotinib combined with nivolumab ( 155 ), camrelizumab ( 156 ), or pembrolizumab ( 157 ).…”
Section: Clinical Characteristics and Treatmentmentioning
confidence: 94%